Voriconazole Susceptibilities of Dermatophyte Isolates Obtained from a Worldwide Tinea Capitis Clinical Trial - Ghannoum, M. (American Society for Microbiology, 2006)
In this study, the voriconazole susceptibilities of dermatophyte isolates obtained from a worldwide tinea capitis trial were compared to their susceptibilities to fluconazole and griseofulvin. The MIC ranges of voriconazole, fluconazole, and griseofulvin, were 0.002 to 0.06 μg/ml, 0.25 to 32 μg/ml, and 0.125 to 2.0 μg/ml, respectively.